Analysis of the clinical features of 980 accidental pediatric injuries in the PICU - Yang, Yufan; Chen, Wang; He, Hengyun; Zhang, Xinping; Huang, Jiaotian; Zhu, Guanghui; Lu, Xiulan; Xiao, Zhenghui (Frontiers in Pediatrics, 2025)
ObjectiveThis study aimed to investigate the causes and clinical characteristics of 980 cases of accidental pediatric injuries admitted to the pediatric intensive care unit (PICU) to provide clinical evidence to support the prevention and reduction of severe accidental pediatric injuries.MethodsA total of 980 patients with accidental pediatric injuries admitted to the pediatric intensive care unit (PICU) of Hunan Children's Hospital from 2017 to 2023 were included in this study.ResultsBetween 2017 and 2023, 980 patients with accidental pediatric injuries were admitted to the PICU, comprising 588 boys and 392 girls (boy-to-girl ratio: 1.5:1). During the study period, a total of 16,151 children were admitted to the PICU, of whom 980 were admitted due to accidental injuries and 15,171 due to non-accidental injuries. There were no statistically significant differences in sex distribution between the accidental and non-accidental injury groups. Accidental pediatric injuries were most common among infants, toddlers, and preschool children, with the number of PICU admissions decreasing with increasing age. Across all years, infants and preschool children were the most affected. Traffic accidents and falls showed an increasing trend over time, whereas poisoning and drowning showed a decreasing trend. Differences in the composition of causes by year were statistically significant. The overall mortality rate among children with accidental injuries was 4.39%. The mortality rates by cause were as follows: traffic accidents (4.2%), falls (3.2%), foreign objects (7.1%), carbon monoxide poisoning (0.0%), food poisoning (9.7%), drug poisoning (1.0%), other types of poisoning (4.2%), burns and corrosive injuries (0.0%), drowning (13.0%), suffocation syndrome (23.1%), and other causes (4.3%). Prognostic differences between causes were statistically significant.ConclusionAccidental pediatric injuries predominantly occur in boys, with infants and preschool children being the most affected. These injuries are more common in summer, with drug poisoning, traffic accidents, and falls being the main causes. Among the common causes, traffic accidents and falls showed an increasing trend, whereas poisoning and drowning showed a decreasing trend. Suffocation syndrome, drowning, and food poisoning were associated with high mortality rates.